Mobile Application Development to Measure Smartphone Screen Readability - Yanto, Yanto; Mulyani, Fransisca Cindy (Metris: Jurnal Sains dan Teknologi, 2019)
This study aimed to develop an application which can be used to measure the response time needed by subjects to find a set of predetermined “words” in order to determine the level of readability of smartphone screen. The development steps began with concept development, interface design and software testing and verification. The results of this study is a software which can be used for typography experiment in which the subject is asked to find a predetermined word. The software could be used for the experiment of 4 typography factors i.e font style (FS), font size (FZ), contrast (CT), and screen rotation (SR). This software could be used for the 5x3x2x2 factorial experiment with 60 combinations. The response time of subject for each treatment combination has been computed and saved in the smartphone. Finally, the response time could be used to determine the best combination of factor and level factor for readability of smartphone screen.